THE IMPACT OF BRAND IDENTITY AND PRICE ON YOUNGER CUSTOMERS' SATISFACTION WITH FOOD TRUCKS IN TERENGGANU - Norazlina binti Rahmat; NurFarzana Athirah binti Rohaizad; Intan Liana binti Ibrahim; Norzaidah binti Ngali (International Journal of Accounting, Finance and Business, 2022)
A food truck is becoming a global business trend and is rapidly growing in Malaysia.Food truck owners are working tirelessly to achieve customer satisfaction through superiorbrand identity and offering competitive prices to make food trucks more recognizable andinteresting to visit, especially among the younger generation. This study aims to analyze theeffect of brand identity and price on younger customers’ satisfaction. An online survey throughGoogle Form was used to collect data. The convenient sampling was chosen, and 124 samplesof the younger generation who visited or purchased from food trucks in Terengganu areinvolved in this study. The findings provide evidence that brand identity and price had apositively significant impact on younger customers’ satisfaction with food trucks. It will assistfood truck owners to improve their brand identity and pricing strategies to increase customersatisfaction, encourage existing customers to return, and attract potential customers